Application of Criminal Sanctions Against Violators Who Resist Officers on Duty in Combating Corona Virus Disease-19 (Covid-19) - Mulya, Ilma; Surya, Achmad (RESAM Jurnal Hukum, 2024)
In anticipation of preventing the transmission of Corona Virus Disease (Covid-19), the public is recommended to implement health protocols through several policies set forth in the regulations. But in reality, some community groups still do not obey the rules of government policy. The purpose of this study is to determine the application of criminal sanctions against violators who fight officers who are on duty in combating corona virus disease-19 (Covid-19). This research is an empirical juridical research using primary data sources and secondary data. The way data is collected is done by interviews and document studies. Data obtained both from literature studies and from field research will be analyzed in a qualitative descriptive manner. The results of the study explained that, the application of criminal sanctions against violators who are on duty in combating corona virus disease-19 (Covid-19), can be charged and can be criminally accounted for with Article 212 of the Criminal Code (KUHP) and Article 93 of Law Number 6 of 2018 concerning Health Quarantine which is punished with a maximum imprisonment of 1 (one) year and/or a maximum fine of Rp.100,000,000,  00 (one hundred million rupiah)".